UZBEK MAHALLA: HISTORY AND MODERN PECULIARITES OF MULTIETHNIC, CONFESSIONAL NEIGHBORHOODS (Scientific journal of the Fergana State University, 2023)
The article discusses the important social institution of the Uzbek people formed over thousands of years - the stages of historical development of the mahalla, the situation in the Soviet era, modern features of growth and democratic development in the years of independence, as well as current issues of mahalla reform in Uzbekistan. The purpose is to study the peculiarities and democratic factors in the organization of the activities of national, religious mahallas, the content and essence of the system of "mahallabay".The research methods as historical, political, philosophical, sociological, psychological, psychological, pedagogical literature, analysis, historical and logical methods of analysis have been used in the study.The research results of the study were the ancient archaeological monuments. The residential complexes within the castle are located along its inner walls, which are divided into 8 neighborhoods along the streets.